El almacenamiento de reportes de operaciones sospechosas por la UAFE y la vulneración del derecho a la presunción de inocencia en Ecuador - Chiriboga Calva, Odalys Katherine (2025)
This article analyses the impact of the storage of Reports of Suspicious Operations (RSO) by the Financial and Economic Analysis Unit (FEAU) in Ecuador on the right to the presumption of innocence, for which a general objective has been proposed that is focussed on developing a critical legal analysis on the relationship between the storage of Reports of Suspicious Operations (RSO) by the Financial and Economic Analysis Unit of Ecuador and the violation of the right to the presumption of innocence, it is known that every person is guilty when there is a final sentence before Is simply considered a suspicious person. To obtain reliable and accurate information, use was made of methods and techniques such as the mixed approach (quali-quantitative), the non-experimental design of a transversal nature, accompanied by the analyticalsynthetic and the inductive-deductive method, as well as the use of interviews and surveys that allowed to collect true information about the subject, problem, and silver objective. The legal analysis of the unconstitutionality action of the 18-18-IN judgement issued by the Constitutional Court of Ecuador, allows us to determine that the right to innocence is not violated despite the fact that the FEAU requests the report of unusual, unjustified or suspicious economic operations, which do not correspond to the economic and financial profile, nor does it violate the right to the protection of personal data stored for ten years in the same Unit, because there are regulations that sanction people who disclose information.